The Volume-Outcome Effect Calls for Centralization of Care in Esophageal Adenocarcinoma: Results From a Large National Cancer Registry. (23rd April 2021) - Han, Samuel; Kolb, Jennifer M.; Hosokawa, Patrick; Friedman, Chloe; Fox, Charlie; Scott, Frank I.; Lieu, Christopher H.; Vajravelu, Ravy K.; McCarter, Martin; Murphy, Caitlin C.; Cook, Michael B.; Gleisner, Ana; et al.
Abstract : INTRODUCTION: Using the National Cancer Database, we assessed the relationship between facility overall esophageal adenocarcinoma (EAC) case volume and survival. METHODS: We categorized facilities into volume quintiles based on annual EAC patient volume and performed a multivariable Cox proportional hazards regression between facility patient volume and survival. RESULTS: In a cohort of 116, 675 patients, facilities with higher vs lower (≥25 vs 1–4 cases) annual EAC patient volume demonstrated improved survival (adjusted hazard ratio: 0.80. 95% confidence interval: 0.70–0.91). DISCUSSION: This robust volume-outcome effect calls for centralization of care for EAC patients at high annual case volume facilities.